2014
DOI: 10.1242/dmm.014951
|View full text |Cite
|
Sign up to set email alerts
|

Heme acts through the Bach1b/Nrf2a-MafK pathway to regulate exocrine peptidase precursor genes in porphyric zebrafish

Abstract: Using a zebrafish model of hepatoerythropoietic porphyria (HEP), we identify a previously unknown mechanism underlying heme-mediated regulation of exocrine zymogens. Zebrafish bach1b, nrf2a and mafK are all expressed in the zebrafish exocrine pancreas. Overexpression of bach1b or knockdown of nrf2a result in the downregulation of the expression of the exocrine zymogens, whereas overexpression of nrf2a or knockdown of bach1b cause their upregulation. In vitro luciferase assays demonstrate that heme activates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Bach1b contains both BTB and BZIP domains and mediates the regulatory role of heme in transcription of the zymogens in zebrafish [17, 18]. Recent study has identified that Bach1b is expressed ubiquitously from one cell to 48 hpf [18], and this observation is consistent with our observation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Bach1b contains both BTB and BZIP domains and mediates the regulatory role of heme in transcription of the zymogens in zebrafish [17, 18]. Recent study has identified that Bach1b is expressed ubiquitously from one cell to 48 hpf [18], and this observation is consistent with our observation.…”
Section: Discussionsupporting
confidence: 92%
“…Bach1b plays an important role in Nrf2-MafK pathway in zebrafish [17]. Thus, we overexpressed Bach1b in zebrafish embryos to investigate the role of Bach1 during vascular development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the findings with nrf1 and nrf2 , zebrafish also possess duplicated keap1 genes ( keap1a and keap1b [227, 229]) and duplicated bach1 genes ( bach1a, bach1b [250, 251]). Together, these results demonstrate that duplicated zebrafish genes are common in the Nrf pathways, as they are in some other pathways involved in regulation of response to environmental stressors [252, 253].…”
Section: Diversity Of Cnc-bzip Transcription Factors and Related Genesupporting
confidence: 76%
“…The expression of nrf2a mRNA at 24 hpf is restricted to the olfactory system, but by 5-dpf this gene is more widely expressed, appearing also in gill, liver, and intestine [266]. Expression of nrf2a mRNA is also seen in the exocrine pancreas at 84 hpf [250]. The expression of nrf3 mRNA is localized to fore, mid- and hindbrain and pectoral fin buds between 24- and 36-hpf [240].…”
Section: Developmental Expression Of Nfe2-related Genes and Induciblementioning
confidence: 99%